Metabolismo in vitro do albendazol em escala miligrama e purificação por cromatografia líquida de alta eficiência semipreparativa - Batistão, Marina Beghini (2012)
This work presents the in vitro metabolism of albendazole (ABZ) conducted with microsomal fractions obtained from Wistar rats and performed in analytical and semipreparative scale. Subsequent separation and purification of the major metabolites was accomplished using High Performance Chiral Liquid Chromatography in normal elution mode. The chromatographic separation of ABZ, albendazol sulphoxide (ABZ-SO), albendazole 2-aminesulphone (ABZ-NH2-SO2) and albendazole sulphone (ABZ-SO2) was achieved on a chromatographic chiral column containing amylose tris(3,5-dimethylphenylcarbamate) (15.0 x 0.46 cm i.d.) or (20.0 x 0.70 cm i.d.), hexane:ethanol (55:45) as mobile phase and = 290 nm. Different parameters in the in vitro biotransformation were evaluated in a univariate mode and the best conditions selected as follows: incubation time (6 hours), concentration of ABZ (1.5 mg/mL), concentration of proteins (20 mg/ml) and concentration of reduced nicotinamide adenine dinucleotide phosphate dehydrogenase (NADPH; 20 mg/ml). For the NADPH regenerating system was used nicotinamide adenine dinucleotide phosphate (NADP) 100 mmol/L, glucose-6-phosphate (G6P) 100 mmol/L and glucose-6-phosphate dehydrogenase (G6PD) 100 U/mL. For the microsomal fractions both the calcium aggregation or ultracentrifugation methods were appropriate for microsome isolation. Ultracentrifugation provided the highest protein concentration for the extracted samples (35.2 mg/mL). The sample preparation was conducted by solid phase extraction and the recoveries were within 89 to 109%. The in vitro metabolism in milligram scale allowed the production of 1.0 mg of the (+)- ABZ-SO and 8.0 mg of the (-)-ABZ-SO. The ABZ-NH2-SO2 and ABZ-SO2 were not observed under the biotransformation conditions tested. The in vitro metabolism in milligram scale can be used for the production and purification of metabolites for further pharmacokinetics studies.